Analisis Tindak Tutur Lokusi dalam Daftar Putar Ruang BK pada Channel YouTube Cerdas Berkarakter Kemendikbud RI - Renny Puspitasari; Elvienchi Multya Dewi; Ain Nina Nur Fahonah; Vivin Widya Sari; Aprilia Maharani; Asep Purwo Yudi Utomo; Rossi Galih Kesuma (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
Speech acts are always closely related to communication with other people. Social interaction is not only carried out directly but can also be done through cyberspace such as social media which can be used as a place to communicate. As a forum for users to easily participate, share and exchange information and ideas in a virtual community and network. This can be used to interact and even to talk about the importance of guidance and counseling services at school. The aim of this research is to determine the locutionary speech acts in the Indonesian Ministry of Education and Culture's Smart Character YouTube videos regarding the topic of counseling guidance (BK). The method used in this research The type of approach used in this research is a qualitative descriptive method by listening, then transcribing the data, identifying, writing and concluding locutionary speech acts. The data source in this research is a talk show on the Indonesian Ministry of Education and Culture's Smart Character YouTube video with the theme BK Room. There are six episodes with the theme Bk room on the YouTube channel. After analyzing the Indonesian Ministry of Education and Culture's Smart Characteristic YouTube video, there are three types of speech acts, namely, statement locution speech acts (declarative), command locution speech acts (imperative), and question locution speech acts (interrogative). This research is expected to help the public to better understand verbal communication regarding each form of speech that is often uttered by someone in the form of locutionary speech act analysis.